Catalonia 2018: Clashing Identities in Public Space - Kubiaczyk , Filip (Studia Europaea Gnesnensia, 2018)
The article analyses the manifestations of underlying identity conflicts in the social spaces of Catalonia, chiefly Barcelona, encountered in the streets, on the sidewalks, motorways, buildings, or beaches. The study focuses on elements that made their appearance after the illegal Catalan independence referendum of October 1st, 2017. Relying on participant observation, the author shows Catalan public space as a domain of semantic and polysemous game, in which struggle for freedom and free speech is the core element.